Penerapan Kode Etik Jurnalistik Dalam Membangun Kepercayaan Publik - S, Ester Esari; Shandy, Shandy (CV. ITTC INDONESIA, 2024)
Mass media has now become an indispensable need and cannot be separated from our activities. Every day we use media to gather information. Intense competition between mass media institutions currently makes it difficult to carry out mass media functions well. This inability can be seen from news packaging that violates the journalistic code of ethics. So the journalistic code of ethics is the foundation of journalist ethics, including rules that direct and guide what journalists can and cannot do in carrying out their journalistic functions. The aim of this research is to analyze the application of the code of ethics in building public trust. This research aims to determine the importance of certain strategies, such as separating facts and opinions. By implementing this strategy consistently, media and journalists can strengthen ties with society and build solid trust. This research uses a qualitative approach, to explore the strategies used to build public trust through implementing a journalism code of ethics. By adhering to ethical principles, the media can increase public trust in the information conveyed and strengthen their role as providers of trustworthy information in society.